Digital Pedagogical Model Based on Climate Change Issues Integrated with Virtual Reality Technology to Enhance Students' Critical Thinking and Climate Change Awareness - Suryati Suryati; Dwi Pangga; Habibi Habibi; Irham Azmi (International Journal of Ethnoscience and Technology in Education, 2025)
Climate change education is crucial for equipping students to tackle pressing global challenges, yet traditional methods often fail to foster critical thinking (CT) and awareness. This study aimed to develop a digital pedagogical model based on climate change issues integrated with Virtual Reality (VR) technology to enhance students' CT and climate change awareness. The research employed a Research and Development (R&D) approach, involving validation, practicality testing, and effectiveness evaluation. Validity data were obtained through expert validation (involving five validators), while practicality and effectiveness data were gathered through implementation processes involving two observers (evaluating model practicality) and 38 high school students (effectiveness test subjects). Implementation utilized a pretest-posttest design and was analyzed descriptively and quantitatively. The findings indicate that the model is valid, with an average validation score of 4.15, and practical, with an implementation score of 4.80 categorized as "very good." The effectiveness test showed significant improvements in students' CT skills, with the average score increasing from the "less critical" to the "moderately critical" category, and in climate change awareness, which rose from the "moderate" to the "high" category. These results highlight the effectiveness of integrating PBL with VR technology in enhancing students’ CT skills and awareness. This study contributes to advancing technology-based education and emphasizes the importance of adopting immersive, problem-based pedagogies in tackling global issues like climate change.